Prophecy and apocalyptic. An annotated bibliography, D. Brent Sandy & Daniel M. O'Hare : book reviews - Deventer, Hans J. M. van (Old Testament essays, 2010)
An annotated bibliography in the technological driven twenty first century immediately raises a few questions : is there still a place in academia for printed works of this nature? Is such an undertaking not doomed to be dated before the publication process even gets underway? Is it possible to cover any field adequately in this way? After reading through this volume one has to acknowledge that questions like these are all answered in a very satisfactory manner. The authors have provided post graduate students and researchers with a valuable tool.